Evolution of Occurrence of Family and Marriage - BERAIA, I.O. (Journal of Advanced Research in Law and Economics; Vol 7 No 8 (2016): JARLE Volume VII, Issue 8(22), Winter 2016, 2017)
The article deals with issues of origin of family, impact of human productive activities on evolution of public relations, which in turn influenced on evolution of family and marriage relationships.